Revisiting the Meaning of the Denominator - Johanning, Debra; Haubert, Lindsey (Ohio Journal of School Mathematics, 2017)
Being able to fluently work with fractions as quantities involves reasoning about the denominator as an indicator of size. This view is emphasized in the Common Core State Standards associated with fractions. This article examines specific classroom problems that can build students’ ability to reason about the denominator as a reference to size.